An Innovative Technology for Provision of Drill-Hole Equipment with Cryogenic-Gravel Filters - Kozhevnikov А.А.; Sudakov А.К. (Science and Innovation, 2024)
Techniques for manufacturing the CGF element and equipping the intake portion of the well with cryogenic-gravel filter have been described. The composition of mineral binder and cryogenically-gravel composite has been substantiated. The influence of physical fields on the properties and technological operations related to equipping the intake portion of the well with CGF and on physical, mechanical, thermal, and technological properties of pilot cryogenic gravel filter element has been established. The parameters of technique for transporting the cryogenic-gravel filter to the intake portion of the well have been theoretically substantiated and experimentally verified.